A19 Early defect of transforming growth factor β1 formation in Huntington's disease. (16th November 2010) - Squitieri, F; Battaglia, G; Cannella, M; Riozzi, B; Orobello, S; Maat-Schieman, M L; Aronica, E; Busceti, C L; Ciarmiello, A; Alberti, S; Sassone, J; Sipione, S; et al.
Abstract : Background: Huntington's disease (HD) is a neurodegenerative disease due to an abnormal accumulation of mutated huntingtin with toxic effects. Neuropathological studies have demonstrated an increased reactivity of astrocytes and oligodendroglial cells, which reflects a process of neuroinflammation and which critically regulate processes of neuronal death and survival by secreting glutamate, neurotrophic factors and cytokines. Aims: A defective expression or activity of neurotrophic factors is contributing to neuronal damage in HD. We extended the analysis to transforming growth factor β1 (TGFβ1), a pleiotropic cytokine with an established role in neuroprotection. Methods: We used two transgenic animal models of HD (R6/2 and YAC128 mice), HD mouse and human brain samples and controls, cell line cultures (astrocytes and striatal knock-in cell lines) and serum from HD subjects. Results: Immunohistochemical analysis of brain cortex from human HD and analysis of human serum showed a reduction in TGFβ1 levels in presymptomatic subjects, which correlate with decreased brain glucose metabolism and loss of white matter volume. TGFβ1 levels increased with the progression of disease up to the late phase of disease being linearly associated with worsening of motor clinical scores and progression rate. We also examined the pharmacological ability of mGlu2/3 receptor agonist (LY379268) to increase production of TGFβ1 levels. In presymptomatic and symptomatic R6/2 mice, LY379268 failed to increase TGFβ1 formation in the cerebral cortex and corpus striatum compared with wild-type mice. Conclusions: These data suggest that TGFβ1 production could be defective in the HD brain and this could contribute to the pathophysiology of neuronal death in HD.